Determination of atmospheric air pollution in the Tbilisi agglomeration using moss bioindicators - Berdzenishvili, Nana ("Intercultural Dialogues" Transactions, 2025)
The paper discusses the ecological state of the atmospheric tank of the Tbilisi agglomeration, which I investigated using bioindicators of Sphagnum - white moss, which is the most sensitive to environmental pollution and which is rare all over the world. The biomonitoring method was used, special measures were taken to prevent pollution from glass, Teflon and steel materials. Monitoring was carried out for three months. The results of the study conducted in Tbilisi and Rustavi showed an increase in the amount of polycyclic aromatic hydrocarbons: pyrene, benzoanthracene, benzaprene, phenols, nitrobenzene, dibenzofuran, pyridine, phthalates, alkylbenzenes, toluene, styrene, xylene, benzene, ethanol, benzaldehydes, acetophenone, benzoic acid and its esters, alkanes, stigmasterol, formamides, furans, furfural, n-hexadecanoic acid and its esters, which are harmful to human health: decreased lung function, poisoning, cancer development.